Factors Influencing Employee Performance at CV Mulia Agung Sentosa: aktor-faktor yang Mempengaruhi Kinerja Karyawan di CV Mulia Agung Sentosa. - Rosa Arvia Susanti; Dewi Andriani (Academia Open, 2024)
This quantitative study aimed to examine the influence of training, rewards, and incentives on employee performance at CV Mulia Agung Sentosa in Mojokerto. Data was collected through questionnaires and interviews from the entire population of 169 employees using a saturated sampling method. The data was analyzed using SPSS version 22 for windows. The results showed that training, rewards, and incentives had a significant effect on employee performance, both partially and simultaneously. The adjusted R Square value was 0.825 or 82.5%, indicating that employee performance was influenced by training, rewards, and incentives by 82.5%, while the remaining 17.5% was influenced by other variables. The findings suggest that companies should invest in training, rewards, and incentives to improve employee performance and increase productivity. Highlight: The study aimed to examine the impact of training, rewards, and incentives on employee performance. Data was collected through questionnaires and interviews from the entire population of 169 employees using a saturated sampling method. The results showed that training, rewards, and incentives had a significant effect on employee performance, both partially and simultaneously, indicating that companies should invest in these factors to improve productivity. Keywords: employee performance, training, rewards, incentives, productivity.